Political and ideological background of LSSR KGB activity against antisoviet powers in 1954-1990 - Kristina Burinskaitė (Lietuvos Istorijos Studijos)
Communist ideology not only legitimized the Soviet totalitarian regime but also influenced and defined the basis and direction of KGB activity and legitimized its repressive policy. Inner and international policy targets of the Communist Party were also important to KGB activity, influencing its operational activity and its methods. The Communist Party was also an important player in forming the repression policy that was implemented by the KGB. Also, the Communist Party obliged the KGB to undertake ideological and political education functions.